(untitled) (South East Asia Journal of Public Health, 2019)
Brick manufacturing industry is considered as one of the fastest-growing industrial sectors posing serious health hazards in most South East Asian countries like Bangladesh. A major portion of brick kilns in Bangladesh are located in and around the Dhaka, one of the world’s most densely populated cities, where the health effects of these brick kilns are obvious but yet not completely known. The study was thus performed based on a structured questionnaire survey to assess the health effects of brick kiln operations on kiln workers and local inhabitants at Baghiya of Konabari union in Gazipur near Dhaka of Bangladesh. A total of 100 randomly selected respondents (70 brick kiln workers and 30 local inhabitants) were surveyed. The results of the survey revealed that wood and coal are mostly used fuel for brick production in the study area. The respondents were suffering from skin disease (28%), headache (20%), eye irritation (10%), lung disease (8%), and respiratory diseases such as, asthma (20%), bronchitis (10%) and others (6%) problems, while skin diseases, asthma and other lung diseases were prevalent in workers, and eye irritation, headache and bronchitis were in inhabitants. Inhabitants (36%) who were living in surrounding areas of brick kilns for more than 20 years and workers (40%) who were residing for less than 5 years were suffering most from various diseases. Health education or awareness programs need to be organized since 77.1% and 63.3% of the workers and inhabitants, respectively, were never participated in any health education or awareness programs, and eco-friendly brick kilns should be installed maintaining the existing rules and regulations for minimizing the impacts of brick kiln operation induced air pollution in this respect. South East Asia Journal of Public Health Vol.8(1) 2018: 32-36